Implementasi Program P5 dalam Mengembangkan Kreativitas Siswa sebagai Perwujudan Profil Pelajar Pancasila - Siti Siska Cutikawati (Universitas Palan, 2025)
Profile of Pancasila students is a character that must be possessed by every student based on Pancasila values. In the Pancasila student profile, there are several programs, including P5 (Pancasila Student Profile Strengthening Project). The P5 dimension focused on in this study is creative. Creativity is the ability to innovate to create something new from something that already exists. In this writing, the researcher uses a qualitative approach through interviews as primary data and then literature studies as secondary data. The results of data obtained from this study indicate that the implementation of the P5 program has succeeded in developing student creativity as a manifestation Profile of Pancasila Students.